“In contrasto con ogni equità” - Maria Antonietta Pranteda (Lexicon Philosophicum)
In the ‘Critical Delucidation’ of the Critique of Practical Reason, Kant sets out a brief discussion of the ‘evil principles’ of moral action that are also imputable based on the free causality of the will to children, as well as to all other persons. This passage is taken into consideration because it represents an alternative explanation of moral evil to the one mainly attributable to natural sensible causes found in the Critique. The coherence of the admission of evil principles with the Kantian doctrine of freedom on the one hand, and the elements of dissimilarity with other assumptions in the work on the other, are discussed. In conclusion, the hypothesis is put forward that the thesis of the evil principles is a partial restatement of ideas formulated by Kant in pre-critical times.